TEOLOGI PEMBEBASAN PALESTINA - Edi Purwanto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
The Theology of Liberation in Palestine has become a phenomenon influencing the dynamics of religion, politics, and identity in Palestine and worldwide. This paper analyzes the connection between Palestinian Liberation Theology and Latin American Liberation Theology, as well as its influence on the perception and participation of Christians in the Palestinian liberation movement. The research method employed is a literature review, focusing on relevant literature search, selection, content analysis, comparison, and critical evaluation. The research findings indicate that Palestinian Liberation Theology shares the same roots as Latin American Liberation Theology, focusing on liberation from oppressive structures and restoring dignity to the oppressed. This theology has strengthened the identity of Palestinian Christians and fostered ecumenical cooperation, motivating them to engage politically in the struggle for Palestinian independence. Practical support from global Christians is reflected in concrete actions and social activities, such as support for the Boycott, Divestment, and Sanctions movement against Israel. Palestinian Liberation Theology has been a source of inspiration and strength for Christians in Palestine and worldwide to advocate for justice and promote sustainable peace in the region.